Investigating the Professional Competency and Reflective Practices of State Islamic Primary School English Teachers - Hery Rahmat (Universitas Islam Negeri (UIN) Mataram, 2018)
Continuous teacher reflection is part of the teachers’ education literature. However, in practice, teachers rarely carry out self-reflection processes to make a number of improvements toward their professional performance. This research aimed to know (1) the professional competency of State Primary Islamic School (MIN) English teachers in Mataram in conducting learning process; (2) the reflective practice of these teachers to improve their professional competencies in conducting learning process. This is a qualitative descriptive research as it describes data of the professional competency and the reflective practice of State Primary Islamic School (MIN) English teachers in Mataram in conducting learning process. To collect data, the reseracher uses observation, interview and dokumentation. The research informen are MIN headmasters, English language teachers, and some students. The data analysis technique used (1) data reduction; (2) data verification; and (3) Conclusion. The reserach result showed that (1) the professional competency of State Primary Islamic School (MIN) English teachers in Mataram in conducting learning process is good enough. It is indicated through implementation of three learning activities (Introduction Activity, Main Activity, and Closing Activity) with the supported activities; (2) There are 3 types of reflective practice done by English teachers of State Primary Islamic School (MIN) in Mataram through learning process namely (a) the use of learning media; (b) the addition of exercise score; and (c) the chianging of exercise content.